214k views
18 votes
To use the elimination method, you can subtract the two equations in a system of equations to eliminate one of the variables.

Subtract the two equations,
x+ y = 7
2 - 3y = 5
What is the resulting equation?

User Sam Leach
by
5.7k points

2 Answers

11 votes

Answer:

  • The resulting equation is '4y = 2'.

Explanation:

Hi there... I understood your "2" as a typo and considering it as x.

  • x + y = 7

-(x - 3y = 5)

  • x + y = 7

-x + 3y = -5

  • => 4y = 2

Hence, the resulting equation is '4y = 2'

Hoped this helped.


BrainiacUser1357

User Siim Kallari
by
5.4k points
11 votes

Answer:

  • (6.5, 0.5)

Explanation:

It seems a typo:

  • x + y = 7
  • x - 3y = 5

Subtract to eliminate x and solve for y:

  • x + y - x + 3y = 7 - 5
  • 4y = 2
  • y = 0.5

Now you can find the value of x:

  • x + 0.5 = 7
  • x = 6.5
User Sean Bannister
by
5.4k points